2006
DOI: 10.1007/s10802-005-9004-9
|View full text |Cite
|
Sign up to set email alerts
|

Deviant Peer Affiliation and Problem Behavior: A Test of Genetic and Environmental Influences

Abstract: This study uses a multitrait, multimethod (MTMM) approach to investigate the genetic and environmental etiologies of childhood deviant peer affiliation (DPA) and problem behavior (PROB). The variability of genetic and environmental estimates by agent and method is also examined. A total of 77 monozygotic and 72 dizygotic twin pairs and each twin's close friend were assessed. The informants included parents, teachers, and twins, and the methods involved questionnaire reports and coder ratings of videotaped dyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 50 publications
(62 reference statements)
3
27
0
Order By: Relevance
“…Indeed, national surveys have consistently shown males to use marijuana at a higher rate than females. As has been observed by others (see Bullock et al, 2006;Nebbitt et al, 2008), the observed difference may be a function of parental supervision, which tends to be stronger for female adolescents. Consistent with previous research (see, for example, Gfroerer et al, 2002), youth who had initiated marijuana at a younger age were more likely to consume marijuana at a higher rate.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Indeed, national surveys have consistently shown males to use marijuana at a higher rate than females. As has been observed by others (see Bullock et al, 2006;Nebbitt et al, 2008), the observed difference may be a function of parental supervision, which tends to be stronger for female adolescents. Consistent with previous research (see, for example, Gfroerer et al, 2002), youth who had initiated marijuana at a younger age were more likely to consume marijuana at a higher rate.…”
Section: Discussionsupporting
confidence: 77%
“…Research has documented similarities in levels of risk behavior among adolescents within the same peer group (see Henrich, Kuperminc, Sack, Blatt, & Leadbeater, 2000). In fact, one of the most consistent and strongest predictors of adolescents' deviate behavior is their peer affiliates (see e.g., Bullock, Deater-Deckard, & Leve, 2006;Henrich et al, 2000;Keenan, Loeber, Zhang, Stouthamer-Loeber, & Van Kammen, 1995;Moss, Lynch, Hardie, & Baron, 2002;Nebbitt, Lombe, & Williams, 2008). For example, Henrich and associates (2000) determined that youth who affiliate with delinquent peers reported a high likelihood of using marijuana.…”
Section: The Environmental Factors and Marijuana Usementioning
confidence: 99%
“…The child's antisocial behaviour would be expected to directly affect later deviant peer interactions and young adult problem behaviour. Recent analyses of a genetically informed longitudinal study, however, did not reveal large genetic effects on association with deviant peers (Bullock, 2002). However, these hypotheses are pursued best with a behaviour-genetic design with solid environmental measures, such as those included in this study.…”
Section: Resultsmentioning
confidence: 88%
“…However, it also is plausible that certain aspects of the environment that promote sibling differentiation operate on the affective and behavioral aspects of an approach motivational system, such as twin differences in parent-child and peer relationships and interaction dynamics. With respect to aggression and antisocial behaviors more generally, candidates for nonshared environment processes include harsh reactive parenting and peer rejection and affiliation (Bullock, Deater-Deckard, & Leve, 2006; Mullineaux, Deater-Deckard, Petrill, & Thompson, in press). However, much remains to be learned about whether such nonshared environmental processes can be identified and replicated across studies (Reiss, Neiderhiser, Hetherington, & Plomin, 2000; Turkheimer & Waldron, 2000).…”
Section: Discussionmentioning
confidence: 99%